Low intensity ultrasound induced apoptosis in MCF-7 breast cancer cell lines - Siti P.M. Bohari,; Hamidreza Aboulkheyr,; E.S.,; Nur S. Johan,; Nursyuhada F. Zainudin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
According to the World Cancer Research Fund International (WCRFI), breast cancer is the most common type of cancer in women worldwide with recorded 1.7 million new cases in 2012. The main line of treatments is still limited to chemotherapy, surgery and radiotherapy which could lead to a wide range of dangerous side effects. This study was conducted to evaluate the effect of low intensity ultrasound (LIUS) on cell proliferation, percentage of living and dead cells and the induction of apoptosis on the MCF-7 cell line with CHO cells as the control for non-cancerous group. In order to achieve the objective of this study, several methods of cell-bioguided assays were used including the MTT assay for cell proliferation, Live/Dead assay for the determination of both live and dead cells and gene expression study for the detection of apoptosis in the cells. The cytotoxicity and Live/Dead assays data provided preliminary data that the LIUS has potential to induce apoptosis in a wide population of breast cancer cells. Furthermore, the LIUS treatment induced the expression of p53-mRNA at a detectable level via qPCR analysis, indicating the activation of apoptosis. In short, our study suggested LIUS dosage used in this study could potentially show positive effects in the induction of apoptosis selectively on the MCF-7 with less harm to the control CHO cells.